Pengembangan Manajemen Pembelajaran Tatap Muka Terbatas di SD Negeri Ketapang - Abwandi, Danar; Anjani, Delia Putri; Apriliyani, Dewi; Firdaus, M. Yaufan; Mustikawati, Rara (ANWARUL, 2022)
School-based management is the result of a translation of School Based Management (SBM) is a political approach that aims to redesign school management by giving power to the Principal in an effort to improve school performance which includes teachers, students, principals and increasing community participation. School-based management is a model of education that provides flexibility for schools to develop and implement educational programs in schools according to their needs through empowering existing resources including community participation so that it better reflects efforts to improve the delivery of educational services in a democratic, transparent and accountable manner. in a real way to achieve educational goals that are more efficient and effective without compromising the goals of National Education.